If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 2 + 6 * 3 = 12 * 3x Reorder the terms for easier multiplication: 2x + 6 * 3 = 12 * 3x Multiply 6 * 3 2x + 18 = 12 * 3x Reorder the terms: 18 + 2x = 12 * 3x Multiply 12 * 3 18 + 2x = 36x Solving 18 + 2x = 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 18 + 2x + -36x = 36x + -36x Combine like terms: 2x + -36x = -34x 18 + -34x = 36x + -36x Combine like terms: 36x + -36x = 0 18 + -34x = 0 Add '-18' to each side of the equation. 18 + -18 + -34x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -34x = 0 + -18 -34x = 0 + -18 Combine like terms: 0 + -18 = -18 -34x = -18 Divide each side by '-34'. x = 0.5294117647 Simplifying x = 0.5294117647
| 18t+13=15t | | 2z=a-bj | | xy=1*3 | | 2.8x+5.6=8.4 | | f(4)=-2x-1 | | x*3x=486 | | (2x+7)(x+5)=0 | | 2x+7y-21=0 | | 2.8+5.6=8.4 | | x-2/4=5/7 | | 7a-4=2a+20 | | http://x-2/4=5/7 | | -4x-14=x+1 | | .25+91=180 | | (4x-9)-(11x+6)=0 | | 35n^2-8n-16=0 | | (2x+3)2-(2x-3)(2x+3)=2(3x-5) | | 35n^2-8n=0 | | 3x+4=-3(4x-8) | | (3x-7)(5x+2)=10 | | 5j+z=3 | | 1/16x-.31 | | 2x=2*24 | | -2+k/4=-4 | | 3y+2x-n=12 | | 5-4a=41 | | 21x+2=14 | | -16X+8X=8X+2 | | 6+30+4x=10 | | n-1-n-2= | | 3w+7w+0= | | 8-1/3p=1/2p |